DNA-damage-associated protein co-expression network in cardiomyocytes informs on tolerance to genetic variation and disease - Omar Darrel Johnson; Sayan Paul; José Angel Gutiérrez; William Kent Russell; Michelle Claire Ward (iScience)
Summary: Cardiovascular disease (CVD) is associated with genetic variants and environmental factors. A consequence of multiple risk factors is DNA damage. To examine how DNA damage influences the cardiomyocyte proteome and its relationship to CVD risk, we treated human induced pluripotent stem cell (iPSC)-derived cardiomyocytes with the DNA-damaging agent doxorubicin (DOX). A network constructed from 4,178 proteins reveals 12 co-expressed modules with 403 hub proteins. Five modules correlate with DOX and associate with RNA processing, chromatin regulation, and metabolism. DOX-correlated hub proteins are depleted for proteins that vary in expression across individuals due to genetic variation but are enriched for proteins encoded by loss-of-function intolerant genes. While not enriched for known CVD risk proteins, DOX-correlated hub proteins are enriched for the physical protein interactors of CVD risk proteins. These data demonstrate that protein connectivity in DNA-damage-associated modules influences the tolerance to genetic variation and supports the use of dynamic networks to explore complex traits.